Relationship between teachers teaching styles and students interest towards integrated living skills subjects in schools - How, Shuw Pying; Mat Rashid, Abdullah (Clute Institute for Academic Research, 2014)
The focus of this study is to determine the relationship of teacher's teaching styles (expert, formal authority, personal model, delegation, and facilitator) towards student's interests in Integrated Living Skills (ILS) subjects. The research is designed to explore the common teaching styles applied by ILS teachers in schools and identify the relationship between teaching styles and the interest it generates towards students in the ILS subjects. Furthermore, the study will also focus on the cluster teaching styles which the students preferred. The study involved 240 students of Form 3 in Lower Secondary School of Puchong Perdana as samples. The instruments used are questionnaires of Grasha-Riechman Teaching Styles Inventory and all the data is processed utilizing SPSS software program to get the frequencies, percentage, mean scores and Pearson product moment correlation. Results show that there is a form of positive relationship between the teaching methods applied and the interest of students in ILS subjects. Several recommendations are made based on the findings of the study.